RANCANG BANGUN SISTEM INFORMASI BERBASIS WEB SEBAGAI MEDIA PROMOSI DIGITAL DAN FASILITAS PEMESANAN LAYANAN JASA PROFESIONAL PT GEOTERRA - Nandar Sah Putra (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2026)
In the context of modern business, the introduction and dissemination of company information to the general public play a crucial role. However, companies often face challenges in addressing the limitations of customers who rely solely on government tenders. Limited access to information leads to potential customers not fully understanding the nature of the business conducted by the company, which in turn can constrain growth and marketing opportunities. Therefore, a more efficient approach is needed to convey company information to the public. This research aims to provide a solution to companies in overcoming information access limitations, with a focus on enhancing exposure in the field of operation and developing company revenue. Through the development of an innovative Company Profile Information System, this objective can be better achieved. This research applies the Waterfall method approach in designing and implementing the Company Profile Information System. This approach is chosen for its ability to provide a clear structure in the development stages, from needs analysis, design, development, testing, to implementation. Information gathering is conducted through various sources, including relevant literature, interviews with relevant parties, and direct observation of processes. The result of this research is the implementation of an efficient and effective Company Profile Information System. This system is capable of providing comprehensive and engaging company information for users and prospective clients. By leveraging technology and accessibility through computers and devices, companies can expand their reach and enhance exposure in their field of operation. Furthermore, the success of the Waterfall method approach in system development has proven to yield solutions that align with the company's needs.